Self-Directed Learner - the Three Pillar Model of Self-Directedness The Three Pillar Model for Developing Self-Directedness - Gavriel, Jennifer (Taylor & Francis, 2005)
Self-directed learning is perhaps the Holy Grail of adult learning and for good reason. Within this seemingly simple phrase lies the battleground for the frustrations of both educator and learner as they work through the difficulties of an unequal and sometimes intense partnership